Epidemiological analysis of mortality in elderly patients hospitalized for femoral fractures in the state of Paraná (Research, Society and Development, 2024)
Aging causes changes in various aspects of the body, making it more susceptible to harmful influences. Femoral fractures, especially in the elderly, are concerning due to significant rates of mobility and mortality. Risk factors include hypertension, physical inactivity, and osteoporosis. With the increasing life expectancy, the elderly population is growing, emphasizing the relevance of these fractures. Post-fracture mortality is associated with age, medical conditions, cognitive status, and time to surgery, analyzed through laboratory tests such as leukocyte levels. The social and economic impact is exacerbated by the high post-hospitalization mortality rate. Additionally, the elderly face complications and a reduction in functional reserve. The prevalence of associated diseases affects 70% of patients, with an average of three complications, increasing the risk of death. Osteoporosis contributes to femoral fractures despite preventive measures. The primary treatment is surgical, aiming for stability in fracture fixation, with the option of prosthetic replacement in specific cases. The article employs fundamental research with an observational approach and quantitative analysis. Its objectives are explanatory, aiming to comparatively assess femur fractures in the elderly, analyze associated risk factors, and examine the expenses of the state of Paraná on hospitalizations for this pathology. Documentary technical procedures are employed throughout the temporal development of the research.